2015
DOI: 10.1155/2015/630397
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Enhanced Busulfan-Induced Apoptosis through Downregulating the Expression of Survivin in Leukemia Stem-Like KG1a Cells

Abstract: Leukemia relapse and nonrecurrence mortality (NRM) due to leukemia stem cells (LSCs) represent major problems following hematopoietic stem cell transplantation (HSCT). To eliminate LSCs, the sensitivity of LSCs to chemotherapeutic agents used in conditioning regimens should be enhanced. Curcumin (CUR) has received considerable attention as a result of its anticancer activity in leukemia and solid tumors. In this study, we investigated the cytotoxic effects and underlying mechanisms in leukemia stem-like KG1a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Furthermore, KG1a cells had a large portion of cells bearing a CD34 + CD38 – immunophenotype which was considered to be characteristic of LSCs. Therefore, KG1a was considered to be a LSCs-like cell line and an ideal cell line for preliminary screening of potential anti-AML stem cell agents [ 28 30 ]. We further examined the potency of alantolactone against KG1a.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, KG1a cells had a large portion of cells bearing a CD34 + CD38 – immunophenotype which was considered to be characteristic of LSCs. Therefore, KG1a was considered to be a LSCs-like cell line and an ideal cell line for preliminary screening of potential anti-AML stem cell agents [ 28 30 ]. We further examined the potency of alantolactone against KG1a.…”
Section: Resultsmentioning
confidence: 99%
“…It is well accepted that leukemia stem cells contribute to a reduced treatment efficacy and also to chemoresistance. The natural product curcumin decreased BIRC5 levels in leukemia stem cell-like KG1a in a combined treatment with busulfan, which may overcome such chemoresistant of leukemia stem cells (Weng et al, 2015). Furthermore, Li and colleagues (Li et al, 2018) observed an association between the presence of C allele of BIRC5 polymorphism rs9904341, but not of rs8073069, and an increased risk of acute leukemia development in a cohort including 182 childhood acute leukemia patients and 200 controls.…”
Section: Leukemiamentioning
confidence: 96%
“…Busulfan (a drug widely used in pre-transplantation stem cell conditioning regimens) also shows little activity against these chemoresistant CD34+ leukemic cells, but curcumin, in the same case, has been shown to increase busulfan-induced apoptosis. This synergistic action could allow a reduction in the required clinical dose of busulfan, with the aim of reducing mortality related to transplant toxicity, as suggested in the conclusion of the study by Weng et al [ 43 ]. This is exactly one of the objectives of integrated hematology: to minimize the chemotherapy needed and, therefore, the toxicity for the patient by exploiting the synergistic effect of available substances, such as nutraceuticals.…”
Section: Myeloid Malignanciesmentioning
confidence: 99%